1997
DOI: 10.1152/ajpheart.1997.273.1.h387
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific endothelial cell uptake of cationic liposome-DNA complexes in mice

Abstract: This study identified the organ and cellular distribution of cationic liposome-DNA complexes injected intravenously into CD-1 mice for gene delivery. DOTIM-cholesterol liposomes were labeled with the fluorescent dye CM-Dil and complexed with plasmid DNA encoding the chloramphenicol acetyltransferase reporter gene. The distribution of the complexes was examined in 29 organs and tissues by fluorescence, confocal, and electron microscopy from 5 min to 24 h after injection. The complexes formed clusters in blood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 20 publications
14
153
1
1
Order By: Relevance
“…We and other groups have also reported that lipoplexes accumulate in the liver and spleen, as well as the lung after intravenous administration and liver Kupffer cells and spleen macrophages are directly involved in the uptake of lipoplexes. [14][15][16][17] These data suggest that these cells may play an important role in the production of proinflammatory cytokines. These cells are also involved in the uptake of adenovirus and cytokine production after intravenous administration of recombinant adenovirus vectors.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 84%
See 1 more Smart Citation
“…We and other groups have also reported that lipoplexes accumulate in the liver and spleen, as well as the lung after intravenous administration and liver Kupffer cells and spleen macrophages are directly involved in the uptake of lipoplexes. [14][15][16][17] These data suggest that these cells may play an important role in the production of proinflammatory cytokines. These cells are also involved in the uptake of adenovirus and cytokine production after intravenous administration of recombinant adenovirus vectors.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 84%
“…Several reports have suggested that intravenously administered DNA-cationic molecule complexes are mainly taken up by liver Kupffer cells. [14][15][16][17] Kupffer cell depletion by GdCl 3 would lead to a reduction in lipoplex accumulation in the liver. We could not find any differences in the accumulation of lipoplex in the spleen (Figure 1c).…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
“…The uptake capability of cationic liposome by the capillary endothelial cells is shown to be highest in the lung, less in the muscle and heart. 27 In addition, the size of the liposomes has also been shown to play important role in the tissue distribution. Reduced distribution to the lung can be achieved by decreasing the size of the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…Kumagai et al (1987) observed a rapid binding and endocytosis of cationized albumin to isolated brain capillaries, suggesting that the anionic barrier facilitates the endothelial absorption and endocytosis of cationic molecules. Cationic liposomes have been demonstrated to be taken up by endothelial cells in an organ-specific pattern with highest accumulation in the lung (McLean et al, 1997). However, angiogenic endothelial cells in tumours and in chronic inflammation revealed a preferential uptake of cationic liposomes, with a high proportion being associated with endothelial fenestrae (Thurston et al, 1998).…”
Section: Molecular Charge-dependence Of Vascular Permeabilitymentioning
confidence: 99%
“…Consequently, the excretion of proteins larger than the renally filterable size may initially require catabolism in the liver; and smaller metabolites can then be filtered and excreted through the kidney (Behr et al, 1995). In addition to liver and kidney, organs such as the lung (McLean et al, 1997) and the immune system may be involved in the clearance of charge modified molecules. Bass et al (1990) have shown that cationization of albumin alters its molecular conformation.…”
Section: Plasma Clearance Of Charged Macromoleculesmentioning
confidence: 99%